Multidimensional Building Information Model for Environmental, Social and Governance Integration: Contractor Perspectives in Johor, Malaysia - Sivaraman Kuppusamy; Ng Xin Yin; Noor Azeyah Dato’ Khiyon; Mustafa Klufallah; TamilSalvi Mari (Journal of Construction in Developing Countries, 2026)
The construction industry plays a critical role in addressing global sustainability challenges, and building information modelling (BIM) offers transformative capabilities to support environmental, social and governance (ESG) objectives. This study investigates contractor perspectives on the use of 3D, 4D and 5D BIM for sustainable construction in Johor, Malaysia. The research aims to identify key benefits, challenges and strategies to enhance BIM adoption while aligning with ESG goals. A quantitative approach was employed using a structured questionnaire distributed to Grade 7 (G7) contractors registered with the Construction Industry Development Board Malaysia (CIDB Malaysia). A total of 120 valid responses were analysed using descriptive statistics and correlation analyses. Findings reveal that BIM contributes significantly to environmental sustainability through waste reduction and efficient resource use, socially by enhancing collaboration and stakeholder engagement, and from a governance perspective by improving transparency and accountability. However, challenges such as high implementation cost, lack of expertise and resistance to change hinder widespread adoption. The study proposes strategies including training, government incentives and better industry awareness to promote BIM integration. The findings contribute to the existing body of knowledge by linking BIM capabilities to ESG objectives, offering valuable insights for policymakers and practitioners in developing countries aiming for sustainable construction transformation.